2019
DOI: 10.1186/s12986-019-0354-7
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin ameliorates atherosclerosis in the low-density-lipoprotein receptor knockout mice by suppression of cholesterol accumulation in macrophage foam cells

Abstract: Background Myricetin, a major flavonoid found in several foods including berries, grapes and wine, exhibited strong antioxidant potency, yet the effect on atherosclerosis is not fully understood. In this study, we examined the effect of myricetin on lipid accumulation in macrophage and atherosclerosis in atherosclerosis-prone low density lipoprotein receptor-deficient ( Ldlr −/− ) mice. Methods Ldlr −/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Our findings were in line with an earlier study where myricetin and other flavonoids prevented plasma LDL from oxidation and reduced macrophage intake of ox-LDL in U937 differentiated cells [34]. Meng and others [35] also observed that myricetin blocks the buildup of cholesterol in foam cells by reduced CD36 expression. Study by Plourde and others explain that preventing foam cell development can be achieved by the inhibition of the oxLDL binding to SRs through nanolipoblockers.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings were in line with an earlier study where myricetin and other flavonoids prevented plasma LDL from oxidation and reduced macrophage intake of ox-LDL in U937 differentiated cells [34]. Meng and others [35] also observed that myricetin blocks the buildup of cholesterol in foam cells by reduced CD36 expression. Study by Plourde and others explain that preventing foam cell development can be achieved by the inhibition of the oxLDL binding to SRs through nanolipoblockers.…”
Section: Discussionsupporting
confidence: 93%
“…Studies reported that myricetin could significantly suppress cholesterol accumulation in macrophage foam cells by inhibition of CD36-mediated ox-LDL uptake (Meng, Wang, Xing, Liu, & Li, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Images of Oil Red O-stained aortas were captured for quantification of areas containing atherosclerotic lesions. The digital images of the entire Oil Red O-stained aortas were evaluated using the ImageJ software [21].…”
Section: Oil Red O Stainingmentioning
confidence: 99%